2017
DOI: 10.1242/jcs.195875
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of the oocyte nucleolus in mice through a single nucleolar protein, NPM2

Abstract: The mammalian oocyte nucleolus, the most prominent subcellular organelle in the oocyte, is vital in early development, yet its key functions and constituents remain unclear. We show here that the parthenotes/zygotes derived from enucleolated oocytes exhibited abnormal heterochromatin formation around parental pericentromeric DNAs, which led to a significant mitotic delay and frequent chromosome mis-segregation upon the first mitotic division. A proteomic analysis identified nucleoplasmin 2 (NPM2) as a dominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 51 publications
1
32
0
Order By: Relevance
“…Essentially, our observations confirmed the results obtained by Ogushi et al (2017) who injected Npm2 mRNA into previously enucleolated mouse oocytes. The embryos where pronuclei contained tiny NPBs did not develop after fertilization.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Essentially, our observations confirmed the results obtained by Ogushi et al (2017) who injected Npm2 mRNA into previously enucleolated mouse oocytes. The embryos where pronuclei contained tiny NPBs did not develop after fertilization.…”
supporting
confidence: 91%
“…Finally, Ogushi et al, (2017) demonstrated that development of zygotes originating from oocytes without NLBs can be rescued by injecting them with Npm2 mRNA. Interestingly, when 1.2mg/ml of mRNA was injected, the pronuclei contained very small NPBs and the zygotes reached the blastocyst stage only sporadically.…”
Section: Towards Clarifying the Role Of Npbs In Zygotesmentioning
confidence: 99%
“…In the absence of NPM2, oocytes and embryos lack NLB and NPB and show defects in heterochromatin structures. Consistent with a role of NPM2 in nucleolus and heterochromatin, a recent study showed that the expression of NPM2 in Npm2-null oocytes sufficed to reconstitute nucleolar structures in enucleolated embryos, and rescued their first mitotic division and full-term development [68].…”
Section: Box 1 Preimplantation Developmental Stagesmentioning
confidence: 59%
“…The removal of NPBs 10 h after sperm injection did not affect embryo development and new nucleoli could form after several cell divisions, suggesting that the nucleoli can originate from de novo synthesized materials [67]. Data also suggest that the developmental defects observed in embryos fertilized with enucleolated oocytes are due to problems with chromosome segregation, mislocalization of centromeric proteins, abnormal first embryonic S-phase progression, and replication stress [44,68]. Consistent with defects linked to genome stability, during the first embryonic cell cycle, embryos lacking NPBs showed a significant reduction in major and minor satellite DNA and a decrease in satellite transcripts by more than half [44].…”
Section: Box 1 Preimplantation Developmental Stagesmentioning
confidence: 93%
“…Further, a few candidate proteins (i.e. NPM2, NCL, SSRP1 and NOLC1) have been found in mouse oocyte NPB (25), together with other key nucleolar proteins (26). Likewise, the somatic nucleolus is rich in small RNAs including microRNAs (miRNAs) (27).…”
Section: The Composition Of the Npb And Potential Mechanisms For Its mentioning
confidence: 99%